2011
DOI: 10.1007/s13181-010-0130-6
|View full text |Cite
|
Sign up to set email alerts
|

Follow-Up Assessment of Health Consequences after a Chlorine Release from a Train Derailment—Graniteville, SC, 2005

Abstract: Introduction After a train derailment released chlorine gas in Graniteville, South Carolina, in 2005, a multiagency team performed an epidemiologic assessment of chlorine exposure and resulting health effects. Five months later, participants were resurveyed to determine their health status and needs and to assist in planning additional interventions in the community. Methods Questionnaires were mailed to 279 patients interviewed in the initial assessment; follow-up telephone calls were made to nonresponders. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 3 publications
0
16
0
1
Order By: Relevance
“…Both instruments study health complaints, not diagnoses, which is of importance when examining assumedly healthy participants. Previous studies showed low agreement between report of symptoms when surveyed twice42 ) , which introduces the risk of recall biases. To minimize such biases, the instruments we used enquired about SHC and PTSS during the previous 30 and 7 days, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Both instruments study health complaints, not diagnoses, which is of importance when examining assumedly healthy participants. Previous studies showed low agreement between report of symptoms when surveyed twice42 ) , which introduces the risk of recall biases. To minimize such biases, the instruments we used enquired about SHC and PTSS during the previous 30 and 7 days, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…Occupational exposure to high concentrations of chlorine gas is rare, and most commonly due to workplace unintentional events or human error. In 2005, 72 persons were hospitalized and 9 died after a train transporting 60 tons of chlorine gas derailed in South Carolina . Additionally, emergency personnel responding to such incidents may be exposed to the hazards without sufficient respiratory protection .…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-two percent of employees reported symptoms consistent with PTSD following an unintentional chlorine gas release at a poultry processing plant in 2011 [NIOSH 2013], and nearly half of respondents reported PTSD symptoms following a train derailment and chlorine gas exposure in South Carolina in 2005 [Duncan et al 2011]. PTSD symptoms have the potential to last many years, with approximately one-third of individuals diagnosed with PTSD displaying symptoms for up to 6 years in one study [Bisson 2007].…”
Section: Discussionmentioning
confidence: 99%